Practice of Buying and Buying Paid Goods With Gold Guarantee in Perspective Islamic Law - Siti Fatimah; Tehedi Tehedi; Wiwin Guanti (INTERNATIONAL JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS (INJOSS), 2022)
This research is motivated by the practice of accounts payable by the seller to the buyer. Based on the results of the study, it can be concluded that the practice of buying and selling goods is paid for with gold collateral in Tebing Batu Village, Sebawi District, by offering from house to house with cash payment systems and accounts payable. The practice of buying and selling also has additional terms and costs if it is past due in making accounts payable. the practice of buying and selling goods paid for with gold collateral in Tebing Batu Village, Sebawi District, has fulfilled the pillars and conditions of the contract, the pillars and conditions of sale and purchase, the pillars and conditions of debt and credit as well as the pillars and conditions of the guarantee. However, the practice of buying and selling goods carried out has additional costs when it is due so that it contains elements of usury nasi'ah.